The kiss of death : Thomas Lovell Beddoes' Death's Jest-book and the Rosicrucian quest : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Dearlove, Sharon Lynn (Massey University, 1993)
Filled with abhorrence at the puny-hearted, mean-minded nature of the individual will and at the termination of human existence and striving under a great clod of dirt, Thomas Lovell Beddoes made it his mission to find an answer to the universal mystery of death - an answer he believed was to be found in nature. Beddoes was not alone in his quest. One group in particular who sought to free humanity from its ills was the Rosicrucians. Death's Jest-Book is a portrayal of the endeavour of the brothers of the Rosy Cross to unmask the secrets of death and become immortal as gods. By placing Beddoes' play in the specific context of Rosicrucianism, this thesis explores the philosophy of self-elevation and its sources, and attempts to refute the view that Beddoes succeeded in making a fool of Death.
Keywords: Beddoes, Thomas Lovell 1803-1849; Rosicrucians